FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA SISWI KELAS IX DI SMP NEGERI 2 GELUMBANG - Reffi Dhamayanti; Eka Afrika (LPPM STIKes Mitra Adiguna, 2026)
Anemia among adolescent girls remains a major public health concern, particularly during school age, as it may impair cognitive performance, academic achievement, and reproductive health in later life. Adolescent girls are more vulnerable to anemia due to increased iron requirements, unbalanced dietary intake, inadequate nutritional status, limited knowledge, and blood loss during menstruation. This study aimed to examine the factors associated with the occurrence of anemia among ninth-grade female students at SMP Negeri 2 Gelumbang in 2025, with independent variables including dietary patterns, nutritional status based on body mass index (BMI), and knowledge. A quantitative study with a cross-sectional design was conducted. The study population consisted of all ninth-grade female students, and samples were selected using a total sampling technique. Data were collected through structured questionnaires, BMI measurements, and hemoglobin (Hb) level assessments. Bivariate analysis was performed using the Chi-Square test. The findings revealed that unbalanced dietary patterns, abnormal nutritional status, and low levels of knowledge were significantly associated with the occurrence of anemia among the students. These results emphasize the importance of implementing nutritional interventions and health education at the school level as effective strategies for preventing anemia among adolescent girls. Keywords: anemia, adolescent girls, dietary pattern, nutritional status, knowledge